2012
DOI: 10.1021/ct300550x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Determination of One-Electron Oxidation Potentials for Nucleic Acid Bases

Abstract: The oxidation potentials for N-methyl substituted nucleic acid bases guanine, adenine, cytosine, thymine, uracil, xanthine, and 8-oxoguanine were computed using B3LYP and CBS-QB3 with the SMD solvation model. Acid-base and tautomeric equilibria present in aqueous solution were accounted for by combining standard redox potentials with calculated pKa and tautomerization energies to produce an ensemble averaged pH dependent potential. Gas phase free energies were computed using B3LYP/aug-cc-pVTZ//B3LYP/6-31+G(d,p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(187 citation statements)
references
References 87 publications
(200 reference statements)
13
174
0
Order By: Relevance
“…The acidity/basicity of a molecular site is important to the chemical and biological processes to know the preferred reactive site. Recent studies [67][68][69][70][71][72] have reported that pKa values calculated using DFT methods match well with experimental values. Hence in the present study, the pKa calculations were carried out for all the sixteen tautomeric forms (protonated) using the B3LYP/6-311++G(2d,2p) level of theory in both gas and liquid phases.…”
Section: Pka Valuessupporting
confidence: 61%
“…The acidity/basicity of a molecular site is important to the chemical and biological processes to know the preferred reactive site. Recent studies [67][68][69][70][71][72] have reported that pKa values calculated using DFT methods match well with experimental values. Hence in the present study, the pKa calculations were carried out for all the sixteen tautomeric forms (protonated) using the B3LYP/6-311++G(2d,2p) level of theory in both gas and liquid phases.…”
Section: Pka Valuessupporting
confidence: 61%
“…One-electron oxidation potentials of these DNA bases were estimated computationally using DFT B3LYP and complete basis set (CBS-QB3) methods incorporating solvation effects using the solvation model density (SMD). However, both of these DFT and CBS-QB3 methods were found to underestimate the one electron oxidation potentials of nucleotide bases in acetonitrile solvent by MUEs of 0.33 and 0.21 eV, respectively [115]. Although the predicted oxidation potentials for these bases with respect to the SHE reference electrode, it should be noted that the absolute potential value used for the SHE was 4.28 eV as reported by Kelly et al, underestimated the experimental values by ~0.2-0.3 eV.…”
Section: Organicsmentioning
confidence: 99%
“…Interesting thing to note here is that the redox reaction of nucleic bases in aqueous solution would more likely to exhibit different tautomeric forms; this further complicates the redox potential prediction in aqueous solution. This problem was overcome by introducing ensemble redox potential, which is actually estimated based on the relative energies of the tautomers in the oxidized and reduced states [115].…”
Section: Organicsmentioning
confidence: 99%
“…(2) is usually determined by using a thermodynamic cycle (Fig. 2) in which the free energy of reaction (1) is separated into the sum of the gas-phase free energy and the difference of solvation free energy between the oxidized and reduced species [12,9]:…”
Section: Experimental Datamentioning
confidence: 99%
“…Several reports show that the widely used B3LYP functional is capable of predicting reliable ionization energies, for aromatic systems, even for difficult cases such as the oxidation of DNA nucleobases, nucleosides and oligonucleotides in solution [11][12][13][14][15][16][17][18]. However B3LYP was found to underestimate oxidation free energies of triphenylamine-based dipolar chromophores for dye-sensitized solar cells, while meta functionals furnished more accurate results [19].…”
Section: Introductionmentioning
confidence: 99%